2016
DOI: 10.1007/s10909-016-1604-y
|View full text |Cite
|
Sign up to set email alerts
|

Slow Oscillations of In-plane Magnetoresistance in Strongly Anisotropic Quasi-Two-Dimensional Rare-Earth Tritellurides

Abstract: Slow oscillations of the in-plane magnetoresistance are observed in the rare-earth tritellurides and proposed as an effective tool to determine the parameters of electronic structure in various strongly anisotropic quasi-two-dimensional compounds. These oscillations do not originate from the small Fermi surface pockets, as revealed usually by the Shubnikov-de-Haas oscillations, but from the entanglement of close frequencies due to a finite interlayer transfer integral tz, which allows to estimate its value. Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…L-K fits of the temperature dependence of the oscillation amplitude above T N yield a very light cyclotron effective mass of m*() = 0.101 to 0.106m e (m e is the free electron mass) and a quantum lifetime up to 12.1 × 10 −14 s, resulting in a mobility up to 2012 cm 2 V −1 s −1 (see table S2). We notice that the SdH oscillations in GdTe 3 have previously been reported in (35). However, in this study, only the  pocket was resolved, resulting in F() ≈ 56 T and m*() ≈ 0.1m e .…”
Section: Resultssupporting
confidence: 43%
“…L-K fits of the temperature dependence of the oscillation amplitude above T N yield a very light cyclotron effective mass of m*() = 0.101 to 0.106m e (m e is the free electron mass) and a quantum lifetime up to 12.1 × 10 −14 s, resulting in a mobility up to 2012 cm 2 V −1 s −1 (see table S2). We notice that the SdH oscillations in GdTe 3 have previously been reported in (35). However, in this study, only the  pocket was resolved, resulting in F() ≈ 56 T and m*() ≈ 0.1m e .…”
Section: Resultssupporting
confidence: 43%
“…[26][27][28][29] The origin of this Fermi surface pocket can be attributed to the reconstruction of the Fermi surface due to the incommensurate CDW, which has been observed through photoemission spectroscopy experiments 26,28 as well as through quantum oscillations of other RTe 3 materials. 35,37,38 Although the angular dependence of the SdH oscillation has not been measured in the present study, it was already demonstrated in a similar tritelluride thin film device, i.e., GdTe 3 35 where the SdH oscillation follows 1= cos h (h is the angle between the applied magnetic field and the layer stacking direction). This indicates a highly 2D geometry of the Fermi pockets.…”
mentioning
confidence: 60%
“…According to Eq. ( 7), with the effective electron mass m * ≈ 0.1m e determined from the temperature dependence of the amplitude of SdH oscillations 62 , and F slow ≈ 3.5T (see Fig. 5 (b,d)), one obtains t b ≈ 1meV .…”
Section: Discussionmentioning
confidence: 91%